Heart Failure Update - Hunt, Sharon Ann; Mancini, Donna; Jessup, Mariell; Abraham, William; Costanzo, Maria; Silver, Marc A. (MD Conference Express, 2005)
Five million people in the United States alone suffer with chronic heart failure (HF), producing in excess of 12 million office visits and 6 million hospital days every year. But advances are at hand that hold promise of ameliorating early disease and producing better outcomes in advanced disease. The new ACC/AHA Guidelines for the Diagnosis and Management of Chronic Heart Failure—the first revision in nearly five years—were released just weeks before the American Heart Association’s 2005 Scientific Sessions convened. In replacing the older term “congestive heart failure” with simply “heart failure,” the guidelines acknowledge the biological complexity that heart failure encompasses, much of which is not specifically “congestive” but rather dynamic, structural, and metabolic. Incorporating results of clinical trials as well as technological advances, the guidelines were discussed by ten physicians in two sessions. (See: http://www.acc.org/clinical/guidelines/failure/index.pdf)